ANALISIS KEKERASAN DALAM BERITA TELEVISI: Studi Kasus dalam Program Berita Lintas Petang MNC TV - Aan Herdiana (CV. Amerta Media, 2019)
Media violence is media content or message that contains elements of violence. The elements of violence are found in several media such as film, television, news, and others. News on television should inform the educative and balanced news to the public. However, there are still many news programs on national television that feature violent scenes in its news shows. For example, in the MNC TV's Lintas Petang TV program, which illustrates the chaotic execution of houses. In the show, there were scenes of violence, such as throwing stones, bursts of tear gas, physical clashes, and others. Violent scenes should not always be a